The unexpected effect of the compound microbial agent NP-M2 on microbial community dynamics in a nonylphenol-contaminated soil: the self-stability of soil ecosystem - Chen,Zhaoliang; Zhang,Juanqin; Lv,Weiguang; Zhang,Hanlin; Li,Shuangxi; Zhang,Haiyun; Shen,Yue; Geng,Chunnu; Bai,Naling (PeerJ, 2024)
Background Nonylphenol (NP) is widely recognized as a crucial environmental endocrine-disrupting chemical and persistent toxic substance. The remediation of NP-contaminated sites primarily relies on biological degradation. Compound microbial products, as opposed to pure strains, possess a greater variety of metabolic pathways and can thrive in a wider range of environmental conditions. This characteristic is believed to facilitate the synergistic degradation of pollutants. Limited research has been conducted to thoroughly examine the potential compatibility of compound microbial agents with indigenous microflora, their ability to function effectively in practical environments, their capacity to enhance the dissipation of NP, and their potential to improve soil physicochemical and biological characteristics. Methods In order to efficiently eliminate NP in contaminated soil in an eco-friendly manner, a simulation study was conducted to investigate the impact of bioaugmentation using the functional compound microbial agent NP-M2 at varying concentrations (50 and 200 mg/L) on the dynamics of the soil microbial community. The treatments were set as follows: sterilized soil with 50 mg/kg NP (CK50) or 200 mg/kg NP (CK200); non-sterilized soil with 50 mg/kg NP (TU50) or 200 mg/kg NP (TU200); non-sterilized soil with the compound microbial agent NP-M2 at 50 mg/kg NP (J50) or 200 mg/kg NP (J200). Full-length 16S rRNA analysis was performed using the PacBio Sequel II platform. Results Both the indigenous microbes (TU50 and TU200 treatments) and the application of NP-M2 (J50 and J200 treatments) exhibited rapid NP removal, with removal rates ranging from 93% to 99%. The application of NP-M2 further accelerated the degradation rate of NP for a subtle lag period. Although the different treatments had minimal impacts on the soil bacterial α-diversity, they significantly altered the β-diversity and composition of the bacterial community. The dominant phyla were Proteobacteria (35.54%–44.14%), Acidobacteria (13.55%–17.07%), Planctomycetes (10.78%–11.42%), Bacteroidetes (5.60%–10.74%), and Actinobacteria (6.44%–8.68%). The core species were Luteitalea_pratensis, Pyrinomonas_methylaliphatogenes, Fimbriiglobus_ruber, Longimicrobium_terrae, and Massilia_sp003590855. The bacterial community structure and taxon distribution in polluted soils were significantly influenced by the activities of soil catalase, sucrase, and polyphenol oxidase, which were identified as the major environmental factors. Notably, the concentration of NP and, to a lesser extent, the compound microbial agent NP-M2 were found to cause major shifts in the bacterial community. This study highlights the importance of conducting bioremediation experiments in conjunction with microbiome assessment to better understand the impact of bioaugmentation/biostimulation on the potential functions of complex microbial communities present in contaminated soils, which is essential for bioremediation success.
Keywords: Nonylphenol; Compound microbial agent; Bioremediation; Soil bacterial community structure; Full-length sequencing; Biological self-stability